Identity Politics of Papuan Indigenous Ethnics in the Position Seizure Contestation: A Case Study of the OPD Structural Positions in the Governmental Bureaucracy in Papua - Snanfi, Ferinandus Leonardo; Darwin, Muhadjir; Setiadi, Setiadi; Ikhwan, Hakimul (Political Science Program, Universitas Negeri Semarang, 2018)
This research was aimed to (1) Know how identity politics of Papua indigenious ethnics of Papua contested to seize structural positions of the OPD (Regional Apparatus Organization) in the governmental organization (2) Know identity politics of Papua indigenous ethnics collaborated with identity politics of non-Papuan ethnics in filling structural position of the OPD in the governmental bureaucracy. The research method used was qualitative i.e. describe, record, analyze, interpret conditions occur today. While data gathering used an observation technique, photos and also interview technique. The research results showed (1) Identity politics practice implemented in the governmental bureaucracy shown along with the existence of dominance of office chief, secretary, structural position and also office with much financial were mostly dominated by MT ethnics. MT ethnics marginalized other Papuan ethnics in positions of office chief, agency, district, secretary, structural position. From the process of marginalized Papuan ethnics were affected by ethnics egoism from village, clans, family, one ethnic and other Papuan ethnics emerge other Papuan ethnics prefer non-Papuan ethnics to collaborate in power in the governmental bureaucrcy. Various powers in the filling of the OPD structural positions in the governmental bureaucracy. The bureaucracy of Papuan governmental bureaucracy was still thick with a cultural primordial, familism, tribalism and margaism. The purpose of ethnics identity politics applied in the governmental bureaucracy include to dominate economic resources that are much such as: Otsus Fund, APBD, PAD, DAK, DAU, governmental projects and programs for self ethnic interest and political groups in the governmental bureaucracy. (2) The filling of the OPD structural position of the governmental bureaucracy. The whole of position percentage data result available in filling the OPD structural position of the governmental bureaucracy, MT ethnics dominate all of positions available. And is followed by non-Papuan ethnics (BS, BN, MR, AN, and TA) that collaborated with MT ethnics in seizing number one and number two chairs in the governmental bureaucracy. Team baperjakat has selected officers who are skilled, good career, professional suitable with country’s civil apparatus. However, all decision to promote officials in the OPD structural position, that guard ethnic contestation in the governmental bureaucracy, in overall policy based on number one and number two persons in the governmental bureaucracy. The purpose of collaboration was to dominate jointly economics resources that are much in the governemntal bureaucracy such as: Otsus Fund, APBD, PAD, DAK, DAU, governmental projects and programs for ther ethnic’s interest and their politics group interest.